PENERAPAN FUNGSI STAFFING DALAM LEMBAGA PENDIDIKAN - FAHMIAH AKILAH (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2018)
Abstract. The function of staffing or purpose of filling a position is an activity to obtain skilled employees who will fulfil vacant positions in the alignment. Charging this site aims that all places have officials who will lead to the tasks in the field so that the target organization can be accomplished. In an association that is always at issue is the duty and authority of an executive. An official is unlikely to carry out all the tasks alone to give some of the works to his subordinates. A designation must be guided by an explicit delegation of authority. Keywords: Staffing and Educational Institution